Re-operation to Stop Bleeding after Cardiac Surgery: Mortality, Source of Bleeding, Outcomes and Effects of Time to Delay Re-Operation - Narongchaikul S (Journal of The Department of Medical Services, 2020)
Background: Cardiac surgery is the operation that usually have a risk for post operative bleeding. If the patients do not get proper care may result in increasing morbidity and mortality. Previously the data about post operative bleeding in Central Chest Institute of Thailand was not established. This study may contributed in developing guideline for cardiac surgeons to decrease post operative bleeding. Objective: The purpose of this study was to identify mortality, the source of bleeding and outcomes of re-operation for stop bleeding. Method: This study was retrospective observational study of medical records of patients who had re-operation for stop bleeding after heart surgery in Central Chest Institute of Thailand. Between September 2015 to June 2019, 178 patients were included in study. Result: The incidence of bleeding was at 5.6%. The most identified source of bleeding were sternum wire 19.5%, vein graft branch 14.5% and internal mammary artery branch 9.5% respectively. The mortality rate of re-operation for stop bleeding was 10.7%. Patients with higher EUROSCORE, in need of urgent or emergency surgery, prolonged time until re-operation were at a higher risk of mortality. Conclusion: Delayed re-operation for stop bleeding resulted increasing mortality, bleeding statistically. This study showed the rate of mortality might be decreased if re-operation for stop bleeding was done within three hours after the criteria was met.